Nickel-cobalt binary precursor and preparation method thereof, lithium ion battery positive electrode material and lithium ion battery
By adjusting the process conditions and using the co-precipitation method, the nickel-cobalt binary precursor material is controlled to form a loose core dense shell, which solves the problem of difficulty in preparing nickel-cobalt binary precursor material and inflexible regulation of the proportion of the finished main elements in the prior art, and realizes the preparation of the positive electrode material of high-performance lithium-ion battery.
Patent Information
- Application Number
- CN202411954876.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art faces the problems of difficult preparation of co-precipitation method and inflexible regulation of the proportion of main elements of the finished product when developing high-performance nickel-cobalt binary precursor materials, which affects the first effect, magnification and cycling performance of the positive electrode materials of lithium-ion batteries.
By adjusting the process conditions, the nickel-cobalt binary precursor material is controlled to form a secondary particle structure with loose inner and dense outer layer. The co-precipitation method is used to carry out the co-precipitation reaction under the protection of inert gas, and the morphological structure control is used for complexing agent solutions such as ammonia water and sodium citrate.
It realizes high-performance preparation of nickel-cobalt binary precursor materials, improves the first-effect, magnification and cyclic performance of the cathode material of lithium-ion batteries, and has a simple and easy process for practical application and batch application.
Smart Images

Figure CN119637965A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a nickel-cobalt binary precursor and a preparation method thereof, a lithium-ion battery positive electrode material and a lithium-ion battery. Background Art
[0002] With the vigorous development of the new energy vehicle industry, the requirements for the energy density and driving range of lithium batteries are constantly increasing. As one of the important means to improve the performance of lithium batteries, high nickel content has received extensive attention and research in recent years. While improving the energy density of lithium-ion batteries, high nickel materials reduce the use of cobalt, further reducing the cost of battery manufacturing; as the Ni content increases, the specific capacity of the electrode will also increase, especially when the Ni content exceeds 80% (molar fraction) of the nickel-rich positive electrode material, which has a high specific capacity (>200mAh·g ~1 )’s advantages.
[0003] High nickel ternary materials mainly include LiNi x Co y Mn z O2(NCM) and LiNi x Co y Al z O 2( There are two series of NCA (Ni / NCA) for NCA ternary materials. Since the bond energy of Al-O bond (512kJ / mol) is higher than that of Mn-O bond (402kJ / mol) in NCM, NCA has better structural stability. The high-temperature mixed lithium sintering process has little effect on the performance of the ternary positive electrode material precursor. The physical and chemical indicators such as the structure, proportion, impurity content, and particle size distribution of the positive electrode material will inherit the corresponding characteristics of the precursor. Therefore, the quality of the precursor directly determines the performance of the final positive electrode material. NCA positive electrode materials are based on NCA ternary or nickel-cobalt binary precursor materials. The general precursor material synthesis process is the co-precipitation method; the solubility products of Ni and Co are similar, so the co-precipitation distribution of Ni and Co is relatively uniform; the solubility product of Al is quite different from the solubility product of Ni and Co. Therefore, the co-precipitation conditions of the three ions of Ni, Co, and Al are relatively narrow, which increases the difficulty of preparing hydroxide precursors by the co-precipitation method. The synthesis difficulty of nickel-cobalt binary precursor materials is relatively low, and the nickel-cobalt binary precursor materials are more flexible in regulating the ratio of the main elements of the finished product during the production of positive electrode materials. Therefore, nickel-cobalt binary precursor materials are one of the key precursor materials for the synthesis of nickel-cobalt-aluminum ternary positive electrode materials. Developing excellent NC binary material precursor materials under the existing material system is one of the keys to achieving technical breakthroughs in the performance improvement of NCA materials. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above technical background and provide a nickel-cobalt binary precursor and a preparation method thereof, a lithium-ion battery positive electrode material and a lithium-ion battery.
[0005] The invention provides a nickel-cobalt binary precursor. The nickel-cobalt binary precursor is a spherical or quasi-spherical particle. The particle consists of an inner core and an outer shell layer. The inner core is a loose porous structure, and the ratio of the inner core diameter to the overall particle diameter is 0.25-0.4; the outer shell layer is a dense structure formed by the aggregation of primary crystal grains, and the primary crystal grains are divergently distributed along the diameter direction of the nickel-cobalt binary precursor, and the aspect ratio of the primary crystal grains is 2.5-4.5.
[0006] The present invention also provides a method for preparing the above-mentioned nickel-cobalt binary precursor, which comprises: under the protection of inert gas, flowing a nickel-cobalt salt solution, a precipitant solution and a complexing agent solution into a base liquid in parallel for a co-precipitation reaction to obtain a nickel-cobalt binary precursor, wherein: the complexing agent solution comprises a first complexing agent solution and a second complexing agent solution, the first complexing agent solution is ammonia water, and the second complexing agent solution is a mixed solution of sodium citrate, sodium nitrilotriacetate, sodium tartrate and sodium dodecylbenzene sulfonate.
[0007] The present invention also provides a lithium ion battery positive electrode material, which is obtained by mixing and calcining the above-mentioned nickel-cobalt binary precursor and raw materials including a lithium source.
[0008] The present invention also provides a lithium ion battery, comprising the above lithium ion battery positive electrode material.
[0009] The present invention has the following beneficial effects.
[0010] The present invention provides a nickel-cobalt binary precursor and a preparation method thereof, a lithium-ion battery positive electrode material and a lithium-ion battery. The present invention forms secondary particles with loose inner layers and dense outer structures by adjusting the process control. The positive electrode material formed by mixing and sintering the nickel-cobalt binary precursor material prepared by the process with an aluminum source and a lithium source has good first efficiency, rate and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0012] Figure 1 This is a scanning electron microscope image of a nickel-cobalt binary precursor prepared by Example 1 of the present invention;
[0013] Figure 2 This is a scanning electron microscope image of a cross section of a nickel-cobalt binary precursor prepared in Example 1 of the present invention;
[0014] Figure 3 This is a scanning electron microscope image of a nickel-cobalt binary precursor prepared in Comparative Example 1 of the present invention;
[0015] Figure 4 This is a scanning electron microscope image of the cross section of the nickel-cobalt binary precursor prepared by comparative example 1 of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0017] The following is a detailed description of a nickel-cobalt binary precursor and a preparation method thereof, a lithium-ion battery positive electrode material, and a lithium-ion battery provided in an embodiment of the present invention.
[0018] In the first aspect, an embodiment of the present invention provides a nickel-cobalt binary precursor, which is a spherical or quasi-spherical particle. The particle consists of an inner core and an outer shell layer, wherein the inner core is a loose porous structure, and the ratio of the inner core diameter to the overall particle diameter is 0.25 to 0.4; the outer shell layer is a dense structure formed by the aggregation of primary grains, and the primary grains are divergently distributed along the diameter direction of the nickel-cobalt binary precursor, and the aspect ratio of the primary grains is 2.5 to 4.5.
[0019] The physicochemical properties and morphological structure of the precursor material have good inheritance, and the physicochemical indicators such as the structure, proportion, particle size, and specific surface area of the positive electrode material will inherit the corresponding characteristics of the precursor. In order to improve the first efficiency, rate, and cycle performance of the NCA positive electrode material, the embodiment of the present invention proposes a nickel-cobalt binary precursor synthesis technology, which forms secondary particles with loose internal and dense outer structures by adjusting the process control. The positive electrode material formed by mixing and sintering the nickel-cobalt binary precursor material prepared by this process with an aluminum source and a lithium source has good first efficiency, rate, and cycle performance.
[0020] In some optional embodiments, the nickel-cobalt binary precursor satisfies at least one of the following (1) to (4):
[0021] (1) The chemical formula of the nickel-cobalt binary precursor is Ni x Co 1~x (OH)2, where: 0.8≤x<1;
[0022] (2) The particle size of the nickel-cobalt binary precursor is 1.5 to 3.5 μm, and the particle size of the core is 0.5 to 1.5 μm;
[0023] (3) The primary grains have a grain thickness of 100 to 250 nm and a length of 300 to 1000 nm;
[0024] (4) The specific surface area of the nickel-cobalt binary precursor is ≥5.0㎡ / g, and the tap density is ≥1.0g / cm 3 .
[0025] In a second aspect, an embodiment of the present invention further provides a method for preparing the above-mentioned nickel-cobalt binary precursor, which comprises: under the protection of an inert gas, flowing a nickel-cobalt salt solution, a precipitant solution and a complexing agent solution into a base liquid in parallel for a co-precipitation reaction to obtain a nickel-cobalt binary precursor, wherein: the complexing agent solution comprises a first complexing agent solution and a second complexing agent solution, the first complexing agent solution is ammonia water, and the second complexing agent solution is a mixed solution of sodium citrate, sodium nitrilotriacetate, sodium tartrate and sodium dodecylbenzene sulfonate.
[0026] The embodiment of the present invention also provides a method for preparing the above-mentioned nickel-cobalt binary precursor, wherein the above-mentioned nickel-cobalt binary precursor is prepared by a coprecipitation method, and two complexing agents, namely a first complexing agent and a second complexing agent, are simultaneously used in the process of coprecipitation. By adjusting the composition ratio of the complexing agents during the coprecipitation process, the synthetic morphology and structure control of the nickel-cobalt binary precursor material can be achieved. The nickel-cobalt binary precursor material prepared by this process can improve the first efficiency, rate and cycle performance of its positive electrode material. In addition, the process is simple and easy to operate and apply in batches, and the particle morphology consistency between different batches synthesized once is high, which is conducive to improving the overall product quality.
[0027] In some optional embodiments, the steps include: under the protection of inert gas, introducing nickel-cobalt salt solution, precipitant solution, first complexing agent solution and second complexing agent solution into the base liquid in parallel to carry out stage I reaction; after the crystal nucleus growth of stage I is completed, reducing the flow of precipitant solution, increasing the stirring rate, increasing the complexing ion content and adjusting the introduction ratio of the first complexing agent solution and the second complexing agent solution, adjusting the reaction pH value, allowing the crystal nucleus to continue to grow, continuing the reaction until a product with a required particle size is obtained, completing the reaction of stage II, and obtaining a nickel-cobalt binary precursor through post-treatment of the precipitate.
[0028] In some optional embodiments, during the coprecipitation reaction, the concentration of the nickel-cobalt salt solution is 0.1-2.2 mol / L, the precipitant solution is a sodium hydroxide solution with a concentration of 5-15 mol / L, the concentration of the first complexing agent solution is 5-10 mol / L, the concentration of the second complexing agent solution is 0.01-0.5 mol / L, and the concentration of the second complexing agent solution is 0.1-2.2 mol / L. 柠檬酸钠 :c 氨三乙酸钠:c 酒石酸钠 :c 十二烷基苯磺酸钠 =4~8:1~2:1~2:2~4.
[0029] In some optional embodiments, the preparation of the base liquid comprises the following steps: adding pure water to a reactor, introducing an inert gas to replace the air, and after the air in the reactor is completely replaced, stirring and heating are turned on, and after the temperature reaches the required level, alkali solution, the first complexing agent solution, and the second complexing agent solution are added to the pure water to adjust the complexing ion concentration and pH value of the solution in the reactor to the target values, thereby obtaining the base liquid;
[0030] Preferably, the temperature of the base solution is 50-80° C., the stirring speed is 200-700 rpm, the pH value is 10.0-13.0, and the concentration of the complex ions in the base solution is 0.1-1.0 mol / L.
[0031] In some optional embodiments, the first stage of the coprecipitation reaction comprises: introducing a nickel-cobalt salt solution, a precipitant solution and a complexing agent solution into the prepared base solution in parallel to perform the first stage reaction, and completing the first stage reaction when the crystal nucleus particle size reaches 0.5 to 1.5 μm;
[0032] Preferably, the ratio of the nickel-cobalt salt solution introduced into the reaction in stage I to the precipitant ion concentration is: 氢氧根离子 / c 金属离子 =2.2~2.7;
[0033] Preferably, the ion concentration ratio of the nickel-cobalt salt solution and the complexing agent solution introduced in stage I is: 络合离子 / c 金属离子 =0.1~0.3;
[0034] Preferably, the concentration of complexing ions in the reactor in the first stage is kept consistent with the concentration of complexing ions in the bottom solution, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.1~0.4.
[0035] In some optional embodiments, the stage II reaction of the coprecipitation reaction comprises: introducing a nickel-cobalt salt solution, a precipitant solution, a first complexing agent solution, and a second complexing agent solution into the solution that has completed the stage I reaction in parallel to carry out the stage II reaction, and when the crystal nucleus particle size reaches 1.5 to 3.5 μm, the stage II reaction is completed;
[0036] Preferably, the stirring rate in the reaction kettle is controlled to be 700-1200 rpm, and the pH value is 10.0-13.0;
[0037] Preferably, the ratio of the nickel-cobalt salt solution introduced into the reaction stage II to the precipitant ion concentration is: 氢氧根离子 / c金属离子 =1.8~2.3;
[0038] Preferably, the ion concentration ratio of the nickel-cobalt salt solution and the complexing agent solution introduced in stage II is: 络合离子 / c 金属离子 =0.3~0.5;
[0039] Preferably, the concentration of complexing ions in the reactor in the second stage is 1 to 2 times that in the first stage, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.01~0.1.
[0040] In a third aspect, an embodiment of the present invention further provides a positive electrode material for a lithium-ion battery, which is obtained by mixing and calcining the above-mentioned nickel-cobalt binary precursor with raw materials including a lithium source.
[0041] In a fourth aspect, an embodiment of the present invention further provides a lithium-ion battery, comprising the above-mentioned lithium-ion battery positive electrode material.
[0042] The present invention will be further described below in conjunction with the embodiments.
[0043] Embodiment 1:
[0044] (1) using deionized water to prepare nickel sulfate and cobalt sulfate into a nickel-cobalt mixed salt solution with a concentration of 1.9 mol / L and a molar ratio of nickel to cobalt ions of Ni:Co=0.9:0.1;
[0045] (2) preparing sodium hydroxide with deionized water to prepare a sodium hydroxide solution with a concentration of 10 mol / L as a precipitant solution;
[0046] (3) diluting ammonia water to 9 mol / L with deionized water as complexing agent solution 1;
[0047] (4) Sodium citrate, sodium nitrilotriacetate, sodium tartrate and sodium dodecylbenzene sulfonate were mixed with deionized water to obtain a 柠檬酸钠 :c 氨三乙酸钠 :c 酒石酸钠 :c 十二烷基苯磺酸钠 =6:1:1:2 dissolved into 0.5 mol / L as complexing agent solution 2;
[0048] (5) Add 1 / 3 of the effective volume of pure water into the reactor, introduce nitrogen for air replacement, turn on stirring and heating, set the stirring rate to 500 rpm, the temperature in the reactor to 60°C, add complexing agent solutions 1 and 2 and precipitant, the bottom solution complexing ion concentration is 0.2 mol / L, and the complexing agent mass concentration ratio is: m 第二络合剂 / m 第一络合剂 =0.30; adjust the pH value of the base solution to 12.5.
[0049] (6) Reaction stage I: Under the conditions of step (5), a nickel-cobalt metal salt solution, a sodium hydroxide solution and a complexing agent solution are introduced. The solution c 氢氧根离子 :c 金属离子 =2.4~2.6, c 络合离子 / c 金属离子 =0.1~0.2, control the complexing ion concentration in the reaction system to be 0.1~0.3mol / L, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.30, and through this reaction the particle size reaches 1.0 μm.
[0050] (7) Reaction stage II: Under the conditions of step (6), the flow rate of the sodium hydroxide solution is reduced, and the nickel-cobalt mixed salt solution and the sodium hydroxide solution are in a C 氢氧根离子 :c 金属离子 =2.0~2.1, control the reaction pH to 11.90; increase the stirring rate to 900rpm, adjust 3) and 4) solution flow control c 络合离子 / c 金属离子 =0.4-0.5, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.05, and adjust the complex ion concentration in the reaction system to 0.4-0.5 mol / L; allow the crystal nuclei to continue growing until the particle size reaches 2.5 μm and terminate the reaction.
[0051] (1) The slurry obtained by the coprecipitation reaction is filtered to form a filter cake, and the obtained filter cake is centrifuged and washed with 2 times the weight of alkaline solution, and then centrifuged and washed several times with 4 times the weight of deionized water. After the impurity content meets the standard, the filter cake is centrifuged and dehydrated. Drying is performed at 130° C. for 10 hours to obtain a dry product, and the nickel-cobalt binary precursor material A is obtained after mixing, screening, and demagnetization.
[0052] Depend on Figure 1 and Figure 2 It can be seen that the nickel-cobalt binary precursor prepared by the scheme in Example 1 has a highly porous and loose structure inside and a relatively dense structure outside. The average length of the primary grains reaches 579.3nm, the average thickness of the primary grains reaches 148.7nm, the aspect ratio reaches 3.90, and the core diameter / particle diameter ratio is 0.35, which is a special morphology structure.
[0053] Embodiment 2:
[0054] (2) using deionized water to prepare a nickel-cobalt mixed salt solution with nickel sulfate and cobalt sulfate having a concentration of 2.0 mol / L and a nickel-cobalt ion molar ratio of Ni:Co=0.95:0.05;
[0055] (3) preparing sodium hydroxide with deionized water to obtain a sodium hydroxide solution with a concentration of 8 mol / L as a precipitant solution;
[0056] (4) diluting ammonia water to 5 mol / L with deionized water as complexing agent solution 1;
[0057] (5) Sodium citrate, sodium nitrilotriacetate, sodium tartrate and sodium dodecylbenzene sulfonate were mixed with deionized water at a temperature of 40 °C. 柠檬酸钠 :c 氨三乙酸钠 :c 酒石酸钠 :c 十二烷基苯磺酸钠 =5:1.5:1:3 dissolved into 0.2 mol / L as complexing agent solution 2;
[0058] (6) Add 1 / 2 of the effective volume of pure water to the reactor, introduce nitrogen for air replacement, turn on stirring and heating, set the stirring rate to 700 rpm, the temperature in the reactor to 70°C, add complexing agent solutions 1 and 2 and precipitant, the bottom solution complexing ion concentration is 0.1 mol / L, and the complexing agent mass concentration ratio is: m 第二络合剂 / m 第一络合剂 =0.40; adjust the pH value of the base solution to 12.6.
[0059] (7) Reaction stage I: Under the conditions of step (5), a nickel-cobalt metal salt solution, a sodium hydroxide solution and a complexing agent solution are introduced. The solution c 氢氧根离子 :c 金属离子 =2.5~2.7, c 络合离子 / c 金属离子 =0.15~0.25, the complexing ion in the reaction system is controlled at 0.2~0.3mol / L, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.40, and through this reaction the particle size reaches 0.5 μm.
[0060] (8) Reaction II: Under the conditions of step (6), the flow rate of the sodium hydroxide solution is reduced to control the nickel-cobalt mixed salt solution to have a C 氢氧根离子 :c 金属离子 =2.1~2.15, control the reaction pH to 12.00; increase the stirring rate to 800rpm, adjust 3) and 4) solution flow control c 络合离子 / c 金属离子 =0.35-0.45, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂=0.03, and adjust the complex ion concentration in the reaction system to 0.4-0.5 mol / L; allow the crystal nuclei to continue growing until the particle size reaches 2.0 μm and terminate the reaction.
[0061] (9) The slurry obtained by the coprecipitation reaction is filtered to form a filter cake, and the obtained filter cake is centrifuged and washed with 3 times the weight of an alkaline solution, and then centrifuged and washed several times with 3 times the weight of deionized water. After the impurity content meets the standard, the filter cake is centrifuged and dehydrated. Drying is performed at 120° C. for 12 hours to obtain a dry product, and the NC precursor material B is obtained after mixing, screening, and demagnetization.
[0062] Embodiment 3:
[0063] (1) using deionized water to prepare nickel sulfate and cobalt sulfate into a nickel-cobalt mixed salt solution with a concentration of 1.8 mol / L and a molar ratio of nickel to cobalt ions of Ni:Co=0.98:0.02;
[0064] (2) preparing sodium hydroxide with deionized water to prepare a sodium hydroxide solution with a concentration of 10 mol / L as a precipitant;
[0065] (3) diluting ammonia water to 9 mol / L with deionized water as complexing agent solution 1;
[0066] (4) Sodium citrate, sodium nitrilotriacetate, sodium tartrate and sodium dodecylbenzene sulfonate were mixed with deionized water to obtain a 柠檬酸钠 :c 氨三乙酸钠 :c 酒石酸钠 :c 十二烷基苯磺酸钠 =5:1.2:1.8:3 ratio dissolved to 0.4 mol / L as complexing agent solution 2;
[0067] (5) Add 1 / 2 of the effective volume of pure water to the reactor, introduce nitrogen for air replacement, turn on stirring and heating, set the stirring rate to 600 rpm, the temperature in the reactor to 65°C, add complexing agents 1, 2 and precipitant, the bottom liquid complexing ion concentration is 0.15 mol / L, and the complexing agent mass concentration ratio is: m 第二络合剂 / m 第一络合剂 =0.20; adjust the pH value of the base solution to 12.2.
[0068] (6) Reaction stage I: Under the conditions of step (5), a nickel-cobalt metal salt solution, a sodium hydroxide solution and a complexing agent solution are introduced. The solution c 氢氧根离子 :c 金属离子 =2.3~2.5, c 络合离子 / c 金属离子 =0.1~0.2, the complexing ion in the reaction system is controlled at 0.15~0.2mol / L, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m第一络合剂 =0.20, and through this reaction the particle size reaches 1.3 μm.
[0069] (7) Reaction II: Under the conditions of step (6), the flow rate of the sodium hydroxide solution is reduced to control the nickel-cobalt mixed salt solution and the sodium hydroxide solution to form a C 氢氧根离子 :c 金属离子 =2.05~2.15, control the reaction pH to 11.8; increase the stirring rate to 800rpm, adjust 3) and 4) solution flow control c 络合离子 / c 金属离子 =0.35-0.45, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.02, and adjust the complex ion concentration in the reaction system to 0.3-0.4 mol / L; allow the crystal nuclei to continue growing until the particle size reaches 3.0 μm and terminate the reaction.
[0070] The slurry obtained by the coprecipitation reaction was filtered to form a filter cake, which was centrifugally washed with 4 times the weight of an alkaline solution, and then centrifugally washed several times with 5 times the weight of deionized water. After the impurity content reached the standard, the filter cake was centrifugally dehydrated to obtain a filter cake. The product was dried at 140°C for 8 hours to obtain a dry product, and the nickel-cobalt binary precursor material C was obtained after mixing, screening, and demagnetization.
[0071] Comparative Example 1:
[0072] Comparative Example 1 is based on Example 1, except that the complexing agent solution 2 is eliminated and only the complexing agent solution 1 is introduced, and the parameters of other steps are not adjusted to obtain a nickel-cobalt binary precursor material D.
[0073] Depend on Figure 3 and Figure 4 It can be seen that in Comparative Example 1, only conventional ammonia complex solution was used to participate in the reaction, and the obtained nickel-cobalt binary precursor had a significantly reduced internal loose structure diameter, the core diameter / particle diameter ratio was only 0.21, and the core porosity was relatively low; the external morphology was denser, and the primary grain thickness reached 267.3 nm, which was significantly thicker than that in Example 1, and the aspect ratio was only 2.22, which was significantly lower than that in Example 1.
[0074] Comparative Example 2:
[0075] Comparative Example 2 is based on Example 2, except that the complexing agent solution 2 is cancelled and only the complexing agent solution 1 is introduced, the adjustment of the complexing ion concentration during the process is cancelled, the complexing ion concentration during the entire reaction is controlled with reference to the complexing ion concentration used in reaction stage II in Example 2, and the process stirring rate is not adjusted. The remaining operations are consistent with Example 2 and are not adjusted to obtain nickel-cobalt binary precursor material E.
[0076] Comparative Example 3:
[0077] Comparative Example 3 adjusts the nickel-cobalt ratio based on Comparative Example 2. The nickel-cobalt ratio is the same as that of Example 3. The remaining operating steps are consistent with Comparative Example 2 to obtain a nickel-cobalt binary precursor material F.
[0078] The prepared nickel-cobalt binary precursor material was uniformly mixed with an aluminum source and a lithium source in a certain proportion, calcined at 600-1000°C for 20 hours, taken out and crushed to finally obtain a positive electrode material, which was then subjected to electrochemical performance measurement. The optimal results are shown in Tables 2 and 3 below.
[0079] Test method:
[0080] (1) The particle morphology, thickness and primary grain length of the precursor material were measured by randomly measuring 20 to 30 primary grains using a JMS-IT100 scanning electron microscope and taking the average value. The test results are shown in Table 1.
[0081] (2) The internal structure of the precursor was detected by ion beam profiling. The precursor particles were cut into sections and the sections were inspected and photographed. The internal structure diameter of the product particles and the average particle diameter were measured. The test results are shown in Table 1.
[0082] (3) The six positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were prepared into slurries according to the ratio of positive electrode material: conductive carbon: polyvinylidene fluoride (PVDF) = 90:5:5, and positive electrode sheets were prepared. Metal lithium sheets were selected as negative electrode materials and assembled into CR2025 button batteries. The electrolyte was 1 mol / L LiPF6 / EC:DEC:DMC = 1:1:1 (V%) (wherein EC is ethylene carbonate, DEC is diethyl carbonate, and DMC is Dimethyl carbonate), after activating for 3 cycles at a rate of 0.1C, the discharge capacity retention rate of the button battery was obtained by cycling 100 times at a rate of 1C, and the discharge capacity at the first 1C cycle and the discharge capacity at the 100th 1C cycle were measured respectively, and the capacity retention rate of 100 cycles under 1.0C conditions was calculated; the calculation formula is: cycle retention rate (%) = 1C discharge capacity at the 100th cycle / 1C discharge capacity at the first cycle * 100%, and the cycle retention rate of the material is obtained. First efficiency = 0.1C first discharge capacity / 0.1C first charge capacity * 100%; wherein, the charge and discharge voltage window is 2.7~4.3V. The rate performance test was carried out according to the charge and discharge procedure of 0.1C*3+0.2C*3+0.5C*3+1.0C*3+2.0C*3+5.0C*3+10.0C*3.
[0083] Test results:
[0084] Table 1 Precursor material particle test data
[0085]
[0086] Table 2 Basic electrical properties of precursor materials and cathode materials
[0087]
[0088] Table 3 Rate performance test data
[0089]
[0090] It can be seen from the above test data that the process method proposed by the present invention can effectively control and adjust the diameter of the loose inner core structure and the morphology of the outer primary grains. The precursor material prepared has a certain improvement in specific surface area compared with the comparative example (i.e., the conventional synthesis process using ammonia solution as the complexing agent solution), which is helpful to improve the rate performance of the positive electrode material. Through the cycle, rate and cycle performance tests of the positive electrode material, the nickel-cobalt binary precursor material prepared by the nickel-cobalt binary precursor synthesis process proposed by the present invention is conducive to improving the cycle, rate and cycle performance of its positive electrode material.
[0091] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A nickel-cobalt binary precursor, characterized in that: The nickel-cobalt binary precursor is a spherical or quasi-spherical particle, which consists of an inner core and an outer shell layer. The inner core is a loose porous structure, and the ratio of the inner core diameter to the overall particle diameter is 0.25 to 0.4; the outer shell layer is a dense structure formed by the aggregation of primary grains, and the primary grains are divergently distributed along the diameter direction of the nickel-cobalt binary precursor, and the aspect ratio of the primary grains is 2.5 to 4.
5.
2. The nickel-cobalt binary precursor according to claim 1, characterized in that: The nickel-cobalt binary precursor satisfies at least one of the following (1) to (4): (1) The chemical formula of the nickel-cobalt binary precursor is Ni x Co 1~x (OH)2, where: 0.8≤x<1; (2) The particle size of the nickel-cobalt binary precursor is 1.5 to 3.5 μm, and the particle size of the core is 0.5 to 1.5 μm; (3) The primary crystal grains have a thickness of 100 to 250 nm and a length of 300 to 1000 nm; (4) The specific surface area of the nickel-cobalt binary precursor is ≥5.0 m2 / g, and the tap density is ≥1.0 g / cm 3 .
3. A method for preparing a nickel-cobalt binary precursor according to claim 1 or 2, characterized in that: It includes: Under the protection of inert gas, a nickel-cobalt salt solution, a precipitant solution and a complexing agent solution are simultaneously introduced into a base liquid for a coprecipitation reaction to obtain a nickel-cobalt binary precursor, wherein the complexing agent solution comprises a first complexing agent solution and a second complexing agent solution, the first complexing agent solution is ammonia water, and the second complexing agent solution is a mixed solution of sodium citrate, sodium nitrilotriacetate, sodium tartrate and sodium dodecylbenzene sulfonate.
4. The preparation method according to claim 3, characterized in that: The following steps are involved: Under the protection of inert gas, nickel-cobalt salt solution, precipitant solution, first complexing agent solution and second complexing agent solution are introduced into the bottom liquid in parallel to carry out the first stage reaction. After the crystal nucleus growth of the first stage is completed, the flow rate of the precipitant solution is reduced, the stirring rate is increased, the complexing ion content is increased, and the introduction ratio of the first complexing agent solution and the second complexing agent solution is adjusted. The reaction pH value is adjusted to allow the crystal nucleus to continue to grow. The reaction is continued until a product with a required particle size is obtained, completing the reaction of the second stage. The precipitate is post-treated to obtain a nickel-cobalt binary precursor.
5. The preparation method according to claim 4, characterized in that: During the coprecipitation reaction, the concentration of the nickel-cobalt salt solution is 0.1-2.2 mol / L, the precipitant solution is a sodium hydroxide solution with a concentration of 5-15 mol / L, the concentration of the first complexing agent solution is 5-10 mol / L, the concentration of the second complexing agent solution is 0.01-0.5 mol / L, and the concentration of the second complexing agent solution is 0.1-2.2 mol / L. 柠檬酸钠 :c 氨三乙酸钠 :c 酒石酸钠 :c 十二烷基苯磺酸钠 =4~8:1~2:1~2:2~4.
6. The preparation method according to claim 5, characterized in that: The preparation of the base liquid comprises the following steps: adding pure water to a reaction kettle, introducing an inert gas to replace the air, and after the air in the reaction kettle is completely replaced, stirring and heating are turned on, and after the temperature reaches the required level, alkali solution, a first complexing agent solution and a second complexing agent solution are added to the pure water to adjust the complexing ion concentration and pH value of the solution in the reaction kettle to the target value, thereby obtaining the base liquid; Preferably, the temperature of the base solution is 50-80° C., the stirring speed is 200-700 rpm, the pH value is 10.0-13.0, and the concentration of the complex ions in the base solution is 0.1-1.0 mol / L.
7. The preparation method according to claim 5, characterized in that: The first stage of the coprecipitation reaction includes: introducing a nickel-cobalt salt solution, a precipitant solution, a first complexing agent solution and a second complexing agent solution into the prepared base solution in parallel to carry out the first stage reaction, and when the crystal nucleus particle size reaches 0.5 to 1.5 μm, the first stage reaction is completed; Preferably, the concentration ratio of the nickel-cobalt salt solution introduced into the first stage of the reaction to the precipitant ion is: 氢氧根离子 / c 金属离子 =2.2~2.7; Preferably, the ion concentration ratio of the nickel-cobalt salt solution and the complexing agent solution introduced in stage I is: 络合离子 / c 金属离子 =0.1~0.3; Preferably, the concentration of complexing ions in the reactor in the first stage is kept consistent with the concentration of complexing ions in the bottom solution, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.1~0.
4.
8. The preparation method according to claim 5, characterized in that: The second stage reaction of the coprecipitation reaction includes: introducing a nickel-cobalt salt solution, a precipitant solution, a first complexing agent solution and a second complexing agent solution into the solution that has completed the first stage reaction in parallel to carry out the second stage reaction, and when the crystal nucleus particle size reaches 1.5 to 3.5 μm, the second stage reaction is completed; Preferably, the stirring rate in the reaction kettle is controlled to be 700-1200 rpm, and the pH value is 10.0-13.0; Preferably, the ratio of the nickel-cobalt salt solution introduced into the reaction stage II to the precipitant ion concentration is: 氢氧根离子 / c 金属离子 =1.8~2.3; Preferably, the ion concentration ratio of the nickel-cobalt salt solution and the complexing agent solution introduced in stage II is: 络合离子 / c 金属离子 =0.3~0.5; Preferably, the concentration of complexing ions in the reactor in the second stage is 1 to 2 times that in the first stage, and the mass concentration ratio of the second complexing agent to the first complexing agent in the reaction system is: m 第二络合剂 / m 第一络合剂 =0.01~0.
1.
9. A positive electrode material for a lithium ion battery, characterized in that: The nickel-cobalt binary precursor according to any one of claims 1 to 2 is mixed with raw materials including a lithium source and calcined to obtain the product.
10. A lithium ion battery, characterized in that: The lithium-ion battery positive electrode material comprises the positive electrode material of claim 9.